Voltage stability enchantment via voltage control by using thyristor controlled series compensator (TCSC) [electronic resource] - 553335 Mohd. Hizham Abu Samah (2010)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2010